Modulating supramolecular structures and topologies of coordination polymers and networks using the iminodiacetic acid substituted aromatic ligands - Walsh, David Paul (Trinity College (Dublin, Ireland). School of Chemistry, 2011)
Chapter 1 introduces the reader to the research area described in this thesis. It puts the work into context and provides appropriate literature references. The chapter details the objectives of the work and presents the reader to the used ligand systems. Chapter 2 describes the synthesis of coordination compounds using the 2- aminodiacetic terephthalic acid (H4adta) ligand. A range of novel coordination complexes are formed under ambient reaction conditions displaying a collection of intricate supramolecular interactions. Two mono-nuclear complexes in K[CoII(Hadta)(H2O)2].MeOH (1) and K[NiII(Hadta)(H2O)2].H2O (2), reveal similar coordination environments, but are characterised by different supramolecular interactions and packing arrangements. In contrast, the compound K[Cu1.5II(adta)(H2O)1.5].H2O (3) contains 1D coordination polymers, which are linked via potassium-oxygen interactions to yield a 3D network structure.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin